2013
DOI: 10.2298/ciceq120210058e
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of ethanol fermentation using Saccharomyces cerevisiae: Response surface methodology and artificial neural network

Abstract: In this study, the capabilities of response surface methodology (RSM) and artificial neural networks (ANN) for modeling and optimization of ethanol production from glucoseusing Saccharomyces cerevisiae in batch fermentation process were investigated. Effect of three independent variables in a defined range of pH (4.2-5.8), temperature (20-40ºC) and glucose concentration (20-60 g/l) on the cell growth and ethanol production was evaluated. Results showed that prediction accuracy of ANN was apparently simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Also, the medium used in the reactor was composed of 50 g L −1 glucose, 0.45 g L −1 NH 4 Cl and 1 g L −1 yeast extract. A buffer solution of potassium hydrogen phthalate (0.1 mol L −1 ) and sodium hydroxide (0.1 mol L −1 ) was prepared to set the pH value to 5.2 . After sterilization, this medium was inoculated with 5% of seed culture and prepared to begin the experiment at 32 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the medium used in the reactor was composed of 50 g L −1 glucose, 0.45 g L −1 NH 4 Cl and 1 g L −1 yeast extract. A buffer solution of potassium hydrogen phthalate (0.1 mol L −1 ) and sodium hydroxide (0.1 mol L −1 ) was prepared to set the pH value to 5.2 . After sterilization, this medium was inoculated with 5% of seed culture and prepared to begin the experiment at 32 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A buffer solution of potassium hydrogen phthalate (0.1 mol L −1 ) and sodium hydroxide (0.1 mol L −1 ) was prepared to set the pH value to 5.2. 3 After sterilization, this medium was inoculated with 5% of seed culture and prepared to begin the experiment at 32°C. Batch fermentation combined with pervaporation was performed in the designed PVMBR (600 mL).…”
Section: Microorganism and Mediummentioning
confidence: 99%
“…They concluded that the application of either RSM or ANN modeling techniques is practical approach with a promising future depending on the objectives to be achieved. Esfahanian et al [24] modeled and optimized ethanol fermentation using saccharomyces cerevisiae. They observed that the prediction by ANN was slightly more precise than RSM based on experimental data.…”
Section: Comparison Of Ann and Rsm In Literaturementioning
confidence: 99%
“…During the experiments, the temperature was maintained at 37±1 C (typical body temperature). The composition and instruction for preparation of the Hank's solution are described elsewhere [23].…”
Section: Electrochemical Measurementsmentioning
confidence: 99%